2019
DOI: 10.1097/aog.0000000000003011
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Cardiomyopathy

Abstract: Peripartum cardiomyopathy is defined by left ventricular dysfunction and development of cardiac failure without a known cause and occurring in the final month of pregnancy and up to 5 months postpartum. Peripartum cardiomyopathy is an important and steadily increasing cause of pregnancy-associated morbidity and mortality. The incidence of peripartum cardiomyopathy in the United States has been estimated recently as 1 in 2,230 births and approximately 1 in 1,000 births worldwide. The etiopathogenesis of peripar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 65 publications
0
37
0
8
Order By: Relevance
“…The incidence has increased over the last 20 years due to improvement in echocardiography diagnostic accuracy and the drastic change in maternal characteristics such as advanced maternal age, increase in assisted reproductive techniques, and multifetal gestation. 2,3 The literature review identified risk factors associated with PPCM such as maternal age of more than 30 years, African descent, gestational hypertension, preeclampsia, tocolysis therapy, multifetal gestation, and cocaine use. Multiparity is associated with PPCM but recent studies showed more than 50% of cases occur in the first two pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence has increased over the last 20 years due to improvement in echocardiography diagnostic accuracy and the drastic change in maternal characteristics such as advanced maternal age, increase in assisted reproductive techniques, and multifetal gestation. 2,3 The literature review identified risk factors associated with PPCM such as maternal age of more than 30 years, African descent, gestational hypertension, preeclampsia, tocolysis therapy, multifetal gestation, and cocaine use. Multiparity is associated with PPCM but recent studies showed more than 50% of cases occur in the first two pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…La cardiomiopatía periparto tiene prevalencia a nivel mundial, con una incidencia que varía según la localización geográfica, en Estados Unidos se presenta con una incidencia de 1 en 1,000 a 1 en 4,000 nacimientos, la cual según estudios es similar en Europa y Asia (2,4,5). Sin embargo, existen puntos geográficos donde la incidencia es considerablemente mayor, específicamente la población de Haití y Nigeria, los cuales presentan 1 en 300 nacimientos y 1 en 100 nacimientos respectivamente (2) lo que habla de una marcada diferencia según etnia.…”
Section: Epidemiologíaunclassified
“…La mayoría presentan signos y síntomas de insuficiencia cardíaca congestiva (5). Los síntomas son muy variados, e incluyen fatiga, disnea de esfuerzo, disnea paroxística nocturna, tos, ortopnea, edema con fóvea en las extremidades inferiores, palpitaciones, dolor torácico, y dolor abdominal debido a la hepatomegalia (1,4). La exploración física suele revelar taquipnea, taquicardia, presión venosa yugular elevada, estertores pulmonares, ritmo de galope y ascitis.…”
Section: Clínicaunclassified
See 1 more Smart Citation
“…En la primera definición formal, la CPP se estableció como una cardiomiopatía que causa el desarrollo de insuficiencia cardiaca en el último mes de embarazo o dentro de los primeros 5 meses postparto (1). Sin embargo, el punto de corte temporal utilizado en esta definición es arbitrario, lo cual puede llevar al subdiagnóstico.…”
Section: Definiciónunclassified